Endovascular treatment of acute basilar artery occlusion: A systematic review and meta‐analysis of first‐line stent retriever versus direct aspiration - Juan Zhang; Yongbin Wang; Yanmei Ju; Hongxin Jiang (Brain and Behavior, 2023)
Abstract Background The best choice between first‐line aspiration and stent retriever for acute basilar artery occlusion remains controversial. This study aims to perform a systematic review and meta‐analysis comparing the stent retriever and direct aspiration about reported recanalization rates and periprocedural complications. Method PubMed, Embase, Web of Science, Cochrane, and Clinical Trials were searched for the studies evaluating the efficacy and safety of first‐line aspiration versus stent retriever for acute basilar artery occlusion. A standard software program (Stata Corporation) was used for end‐point analyses. Statistical significance was defined as a p‐value less than .05. Results A total of 11 studies were involved in the current study, including 1014 patients. Regarding postoperative recanalization, the pooled analysis identified a significant difference in successful recanalization (odds ratio [OR] = 1.642; 95% confidence interval (95% CI): 1.099–2.453; p = .015) and complete recanalization (OR = 3.525; 95% CI: 1.306–2.872; p = .001) between the two groups in favor of the first‐line aspiration. Concerning the complications, the first‐line aspiration could achieve a lower rate of total complication (OR = .359; 95% CI: .229–.563; p < .001) and hemorrhagic complication (OR = .446, 95% CI: .259–.769; p = .004) than stent retriever. No significant difference was observed in postoperative mortality (OR = .966; p = .880), subarachnoid hematoma (OR = .171; p = .094), and parenchymal hematoma (OR = .799; p = .720). In addition, the pooled results revealed a significant difference in procedure duration between the two groups in favor of aspiration (WMD = −27.630, 95% CI: −50.958 to −4.302; p = .020). However, there was no significant difference in favorable outcome (OR = 1.149; p = .352) and rescue therapy (OR = 1.440; p = .409) between the two groups. Conclusion Given that the first‐line aspiration was associated with a higher rate of postoperative recanalization, a lower risk of postoperative complication, and a faster duration of the procedure, these findings support the aspiration may be more secure than a stent retriever.